Review on Wearables to Monitor Foot Temperature in Diabetic Patients - Jesús Martín-Vaquero; Ascensión Hernández Encinas; Araceli Queiruga-Dios; Juan José Bullón; Alfonso Martínez-Nova; Jose Torreblanca González; Cristina Bullón-Carbajo (Sensors, 2019)
One of the diseases that could affect diabetic patients is the diabetic foot problem. Unnoticed minor injuries and subsequent infection can lead to ischemic ulceration, and may end in a foot amputation. Preliminary studies have shown that there is a positive relationship between increased skin temperature and the pre⁻ulceration phase. Hence, we have carried out a review on wearables, medical devices, and sensors used specifically for collecting vital data. In particular, we are interested in the measure of the foot⁻temperature. Since there is a large amount of this type of medical wearables, we will focus on those used to measure temperature and developed in Spain.